HMGB1 downregulation in retinal pigment epithelial cells protects against diabetic retinopathy through the autophagy-lysosome pathway. Issue 2 (1st February 2022) - Feng, Lujia; Liang, Liang; Zhang, Shaochong; Yang, Jinglu; Yue, Yanan; Zhang, Xuedong
ABSTRACT: Diabetic retinopathy (DR) is a serious complication of diabetes mellitus and currently one of the major causes of blindness. Several previous studies have demonstrated that autophagy, which is regulated by HMGB1 (high mobility group box 1), is involved in DR development. However, the role of autophagy in DR is quite complicated in that it promotes pericyte survival in early DR, whereas excessive autophagy causes excess stress and leads to necrosis. Therefore, this study aimed to investigate the relationship between HMGB1, the macroautophagy/autophagy-lysosome pathway, and DR, as well as their underlying molecular mechanisms. In brief, the relationship between high glucose (HG) and the autophagy-lysosome pathway was examined in retinal pigment epithelial (RPE) cells. The relationship was studied by detecting classical autophagic features, and siRNAs targeting HMGB1 and pharmacological regulators were used to explore the role of the autophagy-lysosome pathway in DR development. The results demonstrated that HG inhibited autophagy and diminished the degradative capacity of autophagy due to lysosome membrane permeabilization (LMP). In addition, HMGB1 was found to be involved in LMP via the CTSB (cathepsin B)-dependent pathway, but not the CTSL (cathepsin L)-dependent pathway. Knockdown of HMGB1 expression rescued LMP, restored the degradative capacity of autophagy, decreased the expression of inflammatory factors and VEGF (vascular endothelial growth factor), and protected against apoptosis in RPE cells in the early stages of DR.